2019
DOI: 10.1186/s40425-019-0669-y
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study on the pharmacokinetics of nivolumab in metastatic non-small cell lung cancer, melanoma, and renal cell cancer patients

Abstract: Background Nivolumab is administered in a weight-based or fixed-flat dosing regimen. For patients with non-small cell lung cancer (NSCLC), a potential exposure-response relationship has recently been reported and may argue against the current dosing strategies. The primary objectives were to determine nivolumab pharmacokinetics (PK) and to assess the relationship between drug clearance and clinical outcome in NSCLC, melanoma, and renal cell cancer (RCC). Methods In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 36 publications
3
40
4
Order By: Relevance
“…Hypoalbuminemia is a well-recognized marker of cachexia and elevated protein turnover secondary to chronic systemic inflammatory conditions, as observed in many cancer indications. In contrast with other studies [12,24], we failed to identify albuminemia as an independent variability factor of nivolumab pharmacokinetics, probably because of the low interindividual variability in albuminemia. Depending on the time course of tumor size, inflammation status and ADAs production, nivolumab clearance may vary more or less.…”
Section: Discussioncontrasting
confidence: 99%
“…Hypoalbuminemia is a well-recognized marker of cachexia and elevated protein turnover secondary to chronic systemic inflammatory conditions, as observed in many cancer indications. In contrast with other studies [12,24], we failed to identify albuminemia as an independent variability factor of nivolumab pharmacokinetics, probably because of the low interindividual variability in albuminemia. Depending on the time course of tumor size, inflammation status and ADAs production, nivolumab clearance may vary more or less.…”
Section: Discussioncontrasting
confidence: 99%
“…5 7 8 15-17 Interestingly, an exposure-response relationship was found across tumor types, which was hypothesized to be the result of the interpatient variability of drug clearance (CL). [18][19][20] Indeed, it was observed that patients with a faster drug CL had impaired survival outcomes, irrespective of pembrolizumab dosing. 20 Population PK modeling of PD-1 ICIs has previously been performed on data from phase I-III trials [21][22][23][24] and for nivolumab also on real-world data.…”
Section: Introductionmentioning
confidence: 99%
“…20 Population PK modeling of PD-1 ICIs has previously been performed on data from phase I-III trials [21][22][23][24] and for nivolumab also on real-world data. 19 These previous studies described the pembrolizumab PK Open access using two-compartment models with linear elimination or non-linear time-varying elimination. 23 Population PK parameters were similar among different PD-1 agents.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, for trastuzumab, a postmarketing study at a dose higher than the approved dose did not confirm a better response 21 . There was also confusion in the literature on whether a higher dose of nivolumab should be considered due to an apparent E–R relationship 22–24 …”
mentioning
confidence: 99%